Novel and De Novo Mutations Extend Association of POU3F4 with Distinct Clinical and Radiological Phenotype of Hearing Loss. - Agnieszka Pollak; Urszula Lechowicz; Anna Kędra; Piotr Stawiński; Małgorzata Rydzanicz; Mariusz Furmanek; Małgorzata Brzozowska; Maciej Mrówka; Henryk Skarżyński; Piotr H Skarżyński; Monika Ołdak; Rafał Płoski (PLoS ONE, 2016)
POU3F4 mutations (DFNX2) are the most prevalent among non-syndromic X-linked hearing loss (HL) identified to date. Clinical manifestations of DFNX2 usually comprise congenital HL either sensorineural or mixed, a tendency towards perilymphatic gusher during otologic surgery and temporal bone malformations. The aim of the present study was to screen for POU3F4 mutations in a group of 30 subjects with a suggestive clinical phenotype as well as a group (N = 1671-2018) of unselected hearing loss patients. We also planned to analyze audiological and radiological features in patients with HL caused by POU3F4 defects. The molecular techniques used to detect POU3F4 mutations included whole exome sequencing (WES), Sanger sequencing and real-time polymerase chain reaction. Hearing status was assessed with pure-tone audiometry and auditory brainstem response. Computer tomography scans were evaluated to define the pattern of structural changes in the temporal bones. Six novel (p.Gln27*, p.Glu187*, p.Leu217*, p.Gln275*, p.Gln306*, p.Val324Asp) and two known (p.Ala116fs141*, p.Leu208*) POU3F4 mutations were detected in the studied cohort. All probands with POU3F4 defects suffered from bilateral, prelingual, severe to profound HL. Morphological changes of the temporal bone in these patients presented a similar pattern, including malformations of the internal auditory canal, vestibular aqueduct, modiolus and vestibule. Despite different localization in the POU3F4 gene all mutations severely impair the protein structure affecting at least one functional POU3F4 domain, and results in similar and severe clinical manifestations. Sequencing of the entire POU3F4 gene is recommended in patients with characteristic temporal bone malformations. Results of POU3F4 mutation testing are important not only for a proper genetic counseling, but also for adequate preparation and conduction of a surgical procedure.